Hydration reaction and strength development of calcium sulfoaluminate cement-based mortar cured at cold temperatures. (10th November 2019) - Huang, Guangping; Pudasainee, Deepak; Gupta, Rajender; Victor Liu, Wei
Highlights: Cement mortars were cured in frozen sands to mimic the influence of permafrost. Temperature profiles in calcium sulfoaluminate (CSA) cement mortar were recorded. Hydration reaction of CSA cement cured at cold temperatures was investigated. Hydration reaction of CSA cement was fast regardless of cold curing temperatures. CSA-based mortar achieved fast strength development even at −5 °C and −10 °C. Abstract: The objective of this paper is to investigate the hydration reaction and strength development of calcium sulfoaluminate (CSA) cement mortar cured in various cold temperatures (i.e., 5 °C, 0 °C, −5 °C and −10 °C). In this study, both CSA cement-based and GU (General Use) cement-based mortar samples were cured in wet sands at temperatures of 5 °C, 0 °C, −5 °C and −10 °C. During the investigation, the temperature profiles in both sands and the centers of mortar samples were recorded. In addition, thermogravimetric analysis (TGA) and unconfined compressive strength (UCS) tests were conducted on the samples at 1, 3, 7 and 28 days. The TGA results showed that the hydration reaction rate of GU cement was slow at cold temperatures and decreased with a drop in the curing temperature. However, the hydration reaction of CSA cement was very fast—it was mostly completed within the first 24 h—regardless of the curing temperatures. The UCS test results indicated that the strength development of CSA-based mortar was much faster than that of GU-based mortar. The CSA-based mortar achieved rapid strength development even cured in frozen sands with temperatures at −5 °C and −10 °C. In conclusion, CSA cement can be substituted for GU cement to accelerate the strength development of cement-based materials constructed in cold temperatures.